SELECTION AND IMMOBILIZATION OF ISOLATED ACETIC ACID BACTERIA ON THE EFFICIENCY OF PRODUCING ACID IN INDONESIA - Kapti Rahayu Kuswanto; Sri Luwihana Djokorijanto; Hisakazu - Lino (Joglo, 2013)
Screening of AAB(Acetic acid bacteria) isolates from cane sugar juice in Indonesia for acid and alcohol tolerance was performed. Among the isolates tested, strain INT-7 was observed to grow to as high as 9% acetic acid and 15% alcohol. Based on the screening study, INT-7 is belong to Acetobacter pasteurianus were chosen for vinegar fermentation. The pure culture of strain INT-7 on unpasteurized coconut sap was found to have high acidity (5.42%) compared to pasteurized sap (3.42%). Strain INT-7 exhibited higher acid production of 62.7g/L in 5% ethanol under static condition compared to reference strains JCM 7640 Acetobacter aceti and JCM 7641 A. pasteurianus with 52.3g/L and 30.8g/L acid, respectively. On other study, results revealed the efficiency (2X) of using fermentor for acid formation compared to samples fermented with shaking. In addition, the crude metabolites of INT-7 suggest inhibitory effect against the growth of E.coli and Salmonella sp. but not against S. aureus, while strain of INT-17 metabolites inhibited the growth of all pathogenic bacteria tested. The immobilization of A.pasteurianus strain INT-7 for improving the ethanol resistance was done in the alginate gel. The result showed that optimum condition of A. pasteurianus INT-7 cell entrapped (107CFU/mL) on 3% alginate and the ratio of cell number and alginate solution was 1:3 v/v. The optimum condition of acetic acid fermentation by immobilized cells were initial pH 6.0, ethanol concentration 7.5% (v/v), temperature at 30o C for 7 days produced acetic acid (35.81 g/L) is higher than free cells (16.29 g/L). The efficiency of fermentation by immobilized cells and free cells were 36.73% and 16.71%, respectively.   Keywords: Acetic acid bacteria, selection, immobilization, producing higher acid.